ANALISIS DAMPAK PEMILIHAN KEPALA DAERAH (PILKADA) SECARA LANGSUNG: REFORMULASI SISTEM PEMILIHAN KEPALA DAERAH DI INDONESIA (AN ANALYSIS OF THE IMPACT OF DIRECT ELECTION FOR LOCAL LEADERS: REFORMULATION OF ELECTION FOR LOCAL LEADERS SYSTEM IN INDONESIA): Array - Nanang Permana; Sopwan Ismail; Maulana Hasanudin; Ida Farida (Program Studi Hukum Program Pasca Sarjana, 2020)
The mandate of the Constitution which became the basis for implementing a democratic Regional Head Election contained in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia.. The democratic meaning is then set forth in a law which then regulates the local election mechanism. That currently the PILKADA regime is directly being implemented, there are some weaknesses and negative impacts that we should evaluate in order to build a constitutional democracy and reconstruct the implementation of PILKADA that is in accordance with the social, cultural and geographical system in Indonesia. The problems examined in this study are related to the evaluation of the implementation of direct local elections and reformulation of the local election system in Indonesia. The research method used is normative juridical doctrinal research. The approach used by the writer is the statutory approach and the cash approach. The results of the discussion of this research are that the holding of regional head elections still contains various problems both juridically and sociologically, starting from the huge cost and work burden, the regional head tripping over the law, political money, horizontal conflicts, and inconsistent regional dispute resolution. As a step to reformulate the local election system, it is necessary to carry out together the two direct and indirect regional head elections systems, directly to district / municipal regional head elections, indirectly, provincial level regional head elections where the regional head is elected by the president as the representative of the central government in the region.